The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.joc.9b01333
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Promoted Decarboxylative Sulfonylation of Aromatic Carboxylic Acids with Sodium Sulfinates

Abstract: A novel and efficient synthesis of sulfones was developed via a silver-promoted decarboxylative sulfonylation reaction between aromatic carboxylic acids and sodium sulfinates for the first time. The approach features operational simplicity and good functional group compatibility and uses readily available starting materials. Furthermore, mechanistic studies reveal that the decarboxylative sulfonylation reaction is likely to proceed via a radical mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…[157] The reaction of benzoic acids with sodium sulfinates in the presence of Ag 2 CO 3 also led to diaryl sulfones. [158] p-Dimethoxybenzene 299 was effectively sulfonylated with a wide range of sodium and lithium aryl, hetaryl, and alkyl sulfinates 298 under the action of manganese triacetate in HFIP at room temperature (Scheme 131a), while a mixture of regioisomers 302 and 303 was formed from 2-methyl-4-methoxyanisole…”
Section: Sulfonylation Of Carbocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…[157] The reaction of benzoic acids with sodium sulfinates in the presence of Ag 2 CO 3 also led to diaryl sulfones. [158] p-Dimethoxybenzene 299 was effectively sulfonylated with a wide range of sodium and lithium aryl, hetaryl, and alkyl sulfinates 298 under the action of manganese triacetate in HFIP at room temperature (Scheme 131a), while a mixture of regioisomers 302 and 303 was formed from 2-methyl-4-methoxyanisole…”
Section: Sulfonylation Of Carbocyclesmentioning
confidence: 99%
“…Visible light photoredox‐catalyzed synthesis of diaryl sulfones and arylalkyl sulfones in 48–95% yields from aromatic diazonium salts and aromatic or aliphatic sodium sulfinates in MeCN−H 2 O under an inert atmosphere was developed with the use of eosin Y as the photocatalyst [157] . The reaction of benzoic acids with sodium sulfinates in the presence of Ag 2 CO 3 also led to diaryl sulfones [158] …”
Section: Sulfonylation Of Carbocyclesmentioning
confidence: 99%
“…A silver-promoted decarboxylative sulfonylation reaction between aromatic carboxylic acids and sodium sulfinates was achieved by Zhu group. [51] Preliminary mechanism investigations revealed that the reaction probably proceeded via a radical pathway. In the reaction mechanism, silver not only provided the sulfonyl radical via oxidation of sodium sulfinate, but also assisted the decarboxylation of aromatic carboxylic acid (Scheme 41).…”
Section: Sulfonylation With Arenesmentioning
confidence: 99%
“…A silver‐promoted decarboxylative sulfonylation reaction between aromatic carboxylic acids and sodium sulfinates was achieved by Zhu group [51] . Preliminary mechanism investigations revealed that the reaction probably proceeded via a radical pathway.…”
Section: Sulfonylation Reaction Using Sodium Sulfinatesmentioning
confidence: 99%
“…In addition, the oxidation of sulphides and sulfoxides are efficient methods for the synthesis of diaryl sulfone. 29,30 In addition, diaryl sulfones were synthesized by Nicatalysed photoredox sulnylation of halides, 31 cross coupling of aryl iodide with sulnate salts in the presence of photoredox/ Ni catalyst, 32 Cu-catalyzed direct sulfonylation of indolines, 33 silver-promoted decarboxylative sulfonylation of aromatic carboxylic acids with sodium sulnates, 34 arenes and 3CdSO 4 -$xH 2 O in the presence of P 2 O 5 via mechanochemistry 35 and electrochemical methods. [36][37][38] All of these methods are efficient in synthesis of diaryl sulfones.…”
Section: Introductionmentioning
confidence: 99%